Case Report: MSS colorectal extrahepatic (non-liver) metastases as the dominant population for immunotherapy combined with multi-target tyrosine kinase inhibitors - Liu, Jiayin; Li, Dan; Han, Jing; Zhang, Yin; Zhang, Xue; Fan, Zhisong; Feng, Li; Wang, Long; Jin, Hui; Zuo, Jing; Wang, Yudong (Frontiers in Oncology, 2023)
The dMMR/MSI-H subtype of CRC represents approximately 15% of all cases and 5% of mCRC cases. Due to the high mutation rate of dMMR/MSI-H, tumors are highly immunogenic, enabling them to activate the antitumor response of the immune system. dMMR/MSI-H patients have been reported to be more responsive to immune checkpoint inhibitor (ICI)-based immunotherapy. In the KEYNOTE-016 trial, investigators found that multiple tumors in dMMR benefited from pembrolizumab immunotherapy, and in CRC, pembrolizumab monotherapy resulted in an objective response rate (ORR) in cases of dMMR. The ORR was 0 in patients with pMMR [2]. Furthermore, KEYNOTE-164 and 158 studies confirmed that pembrolizumab produced an ORR of 33% and a long-term survival benefit in previously treated patients with advanced MSI-H CRC[3-4]. Based on the excellent results of five studies including KEYNOTE-016, 164, and 158 trials, the FDA approved pembrolizumab in 2017 for the treatment of patients with solid tumors with MSI-H/dMMR, including CRC. Although the above studies affirmed the benefit of immunotherapy in patients with MSI-H/dMMR CRC, it is not recommended as first-line treatment of advanced patients. For 95% of MSS bowel cancer patients, immunotherapy was not as encouraging as the data for advanced MSI-H/dMMR bowel cancer. In contrast, MSS bowel cancer is still called a cold tumor in the industry, and single-drug immunization has little effect on advanced bowel cancer. Basic research suggests that the level of lymphocytes infiltrating the MSS tumor microenvironment is low, and the immune response is weak. The KEYNOTE-016 phase II study and the KEYNOTE-028 IB study also showed that patients with normal mismatch repair (pMMR) CRC did not respond to pembrolizumab therapy. How to change the immune microenvironment and how to turn a cold tumor into a hot tumor has become the biggest bottleneck in the immunotherapy of advanced CRC. However, recent studies related to combination therapy have raised the possibility of improving the efficacy of immunotherapy in this population. The combination of immunotherapy and small-molecule antiangiogenic targeted therapy has made significant progress. This report describes a typical case of successful MSS treatment with lung metastases of CRC.